Minding other people's business : community attachment and anticipated negative emotion in an extended norm activation model - Rosenthal, Sonny (2021)
This study extended the norm activation model in the context of litter reduction to explain self-managing (e.g., avoiding littering) and other-managing (e.g., picking up litter) behaviors. Although those kinds of behaviors are conceptually distinct, prior research has not explained differences in their prediction. This study addresses that gap by considering the roles of community attachment and anticipated negative emotion in other-managing behavior. The addition of those predictors creates a second explanatory pathway in the norm activation model. Results showed awareness of consequences, ascription of responsibility, and community attachment predicted personal norm (R2 = 0.54), which predicted self-managing behavior (R2 = 0.45). Awareness of consequences, community attachment, and personal norm predicted anticipated negative emotion (R2 = 0.40), which predicted other-managing behavior (R2 = 0.06). Self- and other-managing behaviors were moderately correlated (r = 0.42). These results show distinct pathways to the two different kinds of behaviors. They emphasize the importance of instilling in individuals not only a personal norm, but a sense of belonging in their community. The discussion highlights avenues for future research, proposing further model extension to explain civic engagement as a subset of other-managing behavior.